PITFALLS IN THE DIAGNOSIS OF AMIODARONE-INDUCED THYROTOXICOSIS: PITFALLS IN THE DIAGNOSIS OF AMIODARONE-INDUCED THYROTOXICOSIS - Wahab, Syamim Nabihah Abdul; Sukor, Norlela; Kamaruddin, Nor Azmi (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND One of the lesser known but unique mechanisms of action of amiodarone is its ability to inhibit the 5’deiodinase enzyme that converts T4 into the active T3. Inadvertently, this results in an elevated T4 and a lower T3 which suppresses pituitary TSH, giving the impression of a classic thyrotoxicosis. Only when this peripheral effect is overcome by the explosive release of T4 and T3 that they begin to manifest as amiodarone-induced thyrotoxicosis (AIT). CASE We reviewed the last 11 patients who were treated as presumed AIT in our institution who had an elevated fT4 >22 pmol/L and suppressed TSH <0.27 m IU/L at the time of diagnosis. All of them were treated with carbimazole whilst one was started with dexamethasone. However, when the heart rate, symptoms and signs of thyrotoxicosis as well as fT3 levels were analysed, 8 out of the 11 patients were deemed to have demonstrated harmless peripheral or physiological effects of amiodarone which did not require any active intervention. Only one out of the 8 patients had a heart rate above 70/minute at the time of diagnosis notwithstanding the fact they were on low doses of betablockers (2.5-5 mg of bisoprolol). Three out of the 8 patients had low fT3 whilst the remaining 5 had normal levels of fT3. Out of the 3 who had true AIT, two were treated as type 2 AIT and started on prednisolone whilst the third was treated as type 1 AIT and managed with carbimazole. CONCLUSION One of the pitfalls in managing AIT is the failure to recognise the peripheral effect of amiodarone which produces high T4 and suppressed TSH. Only by analysing the T3 level whilst assessing the heart rate and symptomatology will we be able to discern this phenomenon from that of AIT.